2017
DOI: 10.12784/nzcomjnl53.2017.4.30-37
|View full text |Cite
|
Sign up to set email alerts
|

The core of the core: What is at the heart of hospital core midwifery practice in New Zealand?

Abstract: Background: New Zealand midwives who are employed by District Health Boards and are based in hospitals and maternity units are known as core midwives. Half of New Zealand midwives are employed as core midwives, performing a variety of key roles and, as such, are central to the functioning of maternity services. The sustainability of core midwifery is therefore highly significant for the future of maternity services in New Zealand. Research on sustainable midwifery practice operates as a constructive counterpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 20 publications
(40 reference statements)
2
26
0
Order By: Relevance
“…Other literature also shows that midwives who are not able to work in a way or in a capacity that enables them to combine their personal philosophies and working life, may eventually leave the profession (Cox & Smythe, 2011;Gilkison, McAra-Cooper, Fielder, Hunter & Austin, 2017;Sandall, 1997;Jarosova et al, 2015;Pugh et al, 2013;Curtis, Ball & Kirkham, 2006).…”
Section: 24mentioning
confidence: 99%
“…Other literature also shows that midwives who are not able to work in a way or in a capacity that enables them to combine their personal philosophies and working life, may eventually leave the profession (Cox & Smythe, 2011;Gilkison, McAra-Cooper, Fielder, Hunter & Austin, 2017;Sandall, 1997;Jarosova et al, 2015;Pugh et al, 2013;Curtis, Ball & Kirkham, 2006).…”
Section: 24mentioning
confidence: 99%
“…The clinical skills and attitudes required to protect and promote physiological birth and those required to manage the high technology care which some women require are different skill sets (Milosevic et al, 2020). New Zealand research has identified that core midwives have multiple skills at caring for women with complex health needs, managing emergencies, building relationships and being flexible and adaptable in working with a diverse range of demands (Gilkison et al, 2017).…”
Section: How Core Midwives Are Influenced By Institutional Views Of B...mentioning
confidence: 99%
“…In Aotearoa/New Zealand, research tends to focus on community case-loading midwifery, with little insights into hospital midwifery. Two studies focussing on hospital midwives in Aotearoa/New Zealand do not ask the question of why midwives choose to work in institutional maternity units, however give some insight into this indirectly (Gilkison et al, 2017;Wynn-Williams, 2006). Midwives are sustained in their work as a hospital midwife through developing skills valuable to their work and quickly developing rapport with women in a fast paced, ever-changing environment (Gilkison, McAra-Couper, Hunter & Austin 2017).…”
Section: Identifying the Research Problemmentioning
confidence: 99%
“…Two studies focussing on hospital midwives in Aotearoa/New Zealand do not ask the question of why midwives choose to work in institutional maternity units, however give some insight into this indirectly (Gilkison et al, 2017;Wynn-Williams, 2006). Midwives are sustained in their work as a hospital midwife through developing skills valuable to their work and quickly developing rapport with women in a fast paced, ever-changing environment (Gilkison, McAra-Couper, Hunter & Austin 2017). When exploring why midwives transition work settings, which is an option in the Aotearoa/New Zealand maternity system, the researchers found transitioning from hospital to community midwifery and vice-versa is a tool midwives used to remain professionally sustainable, and remain in midwifery as a profession (Welfare, 2018).…”
Section: Identifying the Research Problemmentioning
confidence: 99%
See 1 more Smart Citation